ANALISIS KINERJA KEUANGAN PT. MUSTIKA RATU, Tbk - -, Ratna Dewi (EKONOMIA, 2018)
PT. Mustika Ratu, Tbk is a manufacturerof cosmetics and health care, this company is a pioneer in developing products using herbal ingredients. Companies are estabblished with the goal of having financial performance to gain profit,  Profits that increase from year to year can motivate investors to invest. Investors can know how a company’s financial performance and compare with other companies, the financial performance of the achievement achieved by the company with a certain period as a result of the work process during the period.            Puspose the research to know the financial performance of PT. Mustika Ratu, tbk  a financial performance improvement year 2012-2016 or wheather the financial performance of the company experienced decrease  in 2012-2016.      This study uses the calculation of financial performance  PT.Mustika Ratu,Tbk view from the ratio of liquidity average current ratio of 2012-2016 has decreased. The avearage profitability ratio of gross profit margin for 2012-2016 has increased.  The average leverage ratio of debt to equity for 2012-2016 has increased. The average activity turnover ratio for 2012-2016 increased.            The result of financial performance assesment of liquidity using current current ratio PT. Mustika Ratu, Tbk year 2012-2016 decreased due to the increase  in current ratio liabilities but not followed by a significant increase in current assets. Profitability ratios using  gross profit margin increased, gross profit margin increased due to company seles decreased followed by decrease in gross profit. The leverage ratio using  debt to equity has increaed due to an increase in  total liabilities but not followed  by an increase in total equity. The activity ratio using total assets turnover has increased due to a decrease in total assets resulting in a decreased in sales.